Role of Open Drain Ditches in the Improvement of Saline Soils of Water Logged Tracts of Matunda Region in Chambal Commanded Area - Darra, B.L.; Singh, Harvinder; Bagda, V.K. (Journal of Soil and Water Conservation, 2022)
Chambal commanded area of Rajasthan switched over to irrigation agriculture from the year 1960-61. After the lapse of 3 to 4 years, the lands started showing the patches of salinity and salinity-alkalinity. The intensity of problem increased every day. The main cause for the impairing of soils and subsequent reduction in the production may be attributed to the water table above critical limits of 300 cm (Shaw, 1952).